PENGARUH PENERAPAN GOOD GOVERNANCE, SISTEM AKUNTANSI KEUANGAN DAERAH, SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA SATUAN KERJA PERANGKAT DAERAH KOTA DENPASAR - Indryanigraha, Putu Elvina Tiara; Dewi, Nyoman Ayu Wulan Trisna (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the influence of Good governance implementation, Regional Financial Accounting System, and Internal Control System on the Quality of Financial Statements in Regional Work Units (SKPD) of Denpasar City. The research is grounded in the importance of transparency and accountability in regional financial management to produce high-quality financial statements. This quantitative research employed primary data collected through questionnaires distributed to the Heads and staff of the Finance Subdivision in SKPDs in Denpasar City. The data were analyzed using multiple linear regression with the help of SPSS software. The results show that, partially, the implementation of Good governance, the Regional Financial Accounting System, and the Internal Control System have a positive and significant effect on the Quality of Financial Statements. These findings suggest that strengthening the application of governance principles, establishing a reliable accounting system, and implementing effective internal controls can enhance the quality of financial reporting in local government institutions. This study implies that policymakers should continuously improve governance practices, accounting procedures, and internal supervision to support public financial accountability.